Dampak Sosial Budaya Wisata Makam Bung Karno terhadap Masyarakat Sekitar - Esti Nur Cahyati; Suhartono Suhartono; Cicik Pramesti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
One of the cities in Indonesia that can be a tourist destination is Blitar City, which is located in East Java province. This city is widely known to the public as the National City because it is closely related to the figure of Proclaimer Bung Karno. Blitar City’s popularity is increasing thanks to the tourist attraction Bung Karno. This research aims to determine the existence and social culture impact of the existence of Bung Karno tourism objects in Blitar, East Java. This research uses qualitative methods with data collection techniques through interviews, observation, and documentation. The research shows that Bung Karno’s grave tourism has a significant impact on the social and cultural aspects of the surrounding community. Social change generation can be seen from various aspects, including the emergence of a variety of businesses and social interaction in the community. Tourism will experience real continuity if sustainable planning, environmental, economic, and social development (so that possible external influences are controlled with continuity) are supported by technology and cultural preservation through festivals, youth mentoring, and social media. Overall, this tourism strengthens social interaction.